The Relationship Among Nutrition Knowledge, Vegetable Diet, Nutrition Status of Don Bosco Elementary Students, Manado - Meity Sasube, Laurensi; Luntungan, Aldian Hein (iora, 2020)
Children in urban area tend to abandon healthy diet, since there are a lot of fast food options available around. In general, children valued the importance of nutrition, but they did not concern the health benefit of foods in food selections. Their dietary quality was not satisfactory, and the diet of most children did not meet the recommended serving requirements for vegetable, fruit, cereal and milk. The purpose of this study was to understand the relationship among Nutrition knowledge, vegetables diet and Nutritional Status of Elementary Students at Don Bosco Catholic School Manado. This is a cross sectional study in which we explored the nutritional status of Don Bosco Elementary Students based on nutrition knowledge, vegetable diet and Body Mass Index with questionnaire instrument, anthropometric measurements from June to August 2019. The nutritional status of Don Bosco Elementary School students based on body mass index (BMI) shows that students with normal and overweight nutritional status share an equal comparison that is 1:1 (50%), while the level of student knowledge about nutrition was dominated by students with poor knowledge that is 67.7%. This is also in line with the pattern of vegetables consuming which is also poor at 56.3%. Based on the results of Chi-Square analysis there is no significant relationship between the levels of nutritional knowledge of students with vegetable consumption patterns. Conversely, there is no relationship between the levels of nutritional knowledge of students with nutritional status based on Body Mass Index (BMI).